The effect of thermocycling on fracture toughness and hardness of different core build up materials - G S Shanthala; Mathew K Xavier (Wolters Kluwer Medknow Publications, 2013)
Introduction: Core build up materials are routinely used to restore grossly decayed teeth and in the oral environment they are subjected to changes in the temperature due to consumption of hot and cold food. Aims: The purpose of this study was to determine the effect of thermocycling on the fracture toughness and hardness of 5 core build up materials. Materials and Methods: Fifteen specimens were prepared for each of the following materials: DPI alloy, Miracle-mix, Vitremer, Fuji II LC and Photocore. American Standard for Testing Materials guidelines were used for the preparation of single-edge notch, bar-shaped specimens. Ten specimens of each material were thermocycled for 2000 cycles and the other 5 specimens were not thermocycled (non-thermocycled group). All specimens were subjected to 3-point bending in a universal testing machine. The load at fracture was recorded and the fracture toughness (K IC ) was calculated. Vickers hardness test was conducted on the thermocycled and non-thermocycled group specimens. Results: Photocore had the highest mean K IC in both thermocycled and non-thermocycled groups. Miracle-mix demonstrated the lowest mean fracture toughness (K IC ) for both thermocycled and non-thermocycled groups. By applying Mann Whitney 'U' test the Vickers hardness value in all materials used in the study is highly superior in non-thermocycled group as compared to thermocycled group (P < 0.01). Non-thermocycled Photocore showed highest hardness values of 87.93. Vitremer had lowest hardness of 40.48 in thermocycled group. Conclusion: Thermocycling process negatively affected the fracture toughness and hardness of the core build-up materials.